2020
DOI: 10.1002/ijfe.1895
|View full text |Cite
|
Sign up to set email alerts
|

Do investors herd? An examination of Pakistan stock exchange

Abstract: The study attempts to examine herding behaviour in Pakistan stock exchange and determine how herding behaviour responds to asymmetric market conditions. This study has employed CH model, CSSD & CSAD models, and State‐space model. We have used time series data for the period from 2000 to 2016, which include daily returns of KSE all share index and 890 firms listed on Pakistan stock exchange. The outcomes of the study not only reported significant evidence of herding behaviour in Pakistan stock market over the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Investors cannot fully abandon themselves from emotions, even if they want to make decisions based on models of technical analysis, they still have to make certain assumptions to establish a specific value (Bouteska, 2019; Ren et al , 2018). Investment sentiments such as fears, greed, and overreaction to bad news also play a major role in influencing investment decisions in extreme market conditions (Kashif et al , 2020). Thus by better understanding the drivers of herding via the consideration of investor sentiment, market participants are better able to identify the situations that result in herding, and the findings provide a deeper understanding of financial markets (Garcia, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investors cannot fully abandon themselves from emotions, even if they want to make decisions based on models of technical analysis, they still have to make certain assumptions to establish a specific value (Bouteska, 2019; Ren et al , 2018). Investment sentiments such as fears, greed, and overreaction to bad news also play a major role in influencing investment decisions in extreme market conditions (Kashif et al , 2020). Thus by better understanding the drivers of herding via the consideration of investor sentiment, market participants are better able to identify the situations that result in herding, and the findings provide a deeper understanding of financial markets (Garcia, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In support of the above argument, some authors also revealed that investor sentiment may lead to investor overreaction and/or underreaction (Barberis et al , 1998) or that investors who are overconfident suffer from self-attribution bias (Daniel et al , 1998). Kashif et al (2020) depicted in their study that investment decisions in extreme market conditions are influenced by investor sentiments such as fears, greed, and overreaction to bad news, which portrayed the Pakistan stock market as inefficient and indicating misleading asset prices. Garcia (2021) in their study contributes to the behavioral finance literature by establishing a link between firm-level investor sentiment and analyst herding.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In empirical literature, herding model is estimated using linear approach (see (Arslan and Javid, 2020;Chang et al, 2000;Christie and Huang, 1995;Galariotis et al, 2015;Hwang and Salmon, 2004;Kashif et al, 2020) as well as nonlinear approaches of Markow regime switching (Babalos et al, 2015;Balcilar et al, 2013) and Bai-Perron (Yasir and € Onder, 2021). The UK stock exchange performed good and remained stable till the COVID'19 pandemic, however during the pandemic the stock market volatility increased.…”
Section: Investigation Of Herding Behaviormentioning
confidence: 99%
“…In empirical literature, herding model is estimated using linear approach (see (Arslan and Javid, 2020; Chang et al ., 2000; Christie and Huang, 1995; Galariotis et al ., 2015; Hwang and Salmon, 2004; Kashif et al ., 2020) as well as nonlinear approaches of Markow regime switching (Babalos et al ., 2015; Balcilar et al ., 2013) and Bai-Perron (Yasir and Önder, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The performance of Pakistan stock exchange fluctuated by the political instability (Khan et al 2022;Sulehri and Ali 2020;Mehmood et al 2020) and financial events effect (Kashif et al 2021;Ghouse et al 2019). A total of 19 out of 21 political and financial events have significantly generated high volatility and only 2 events are insignificant.…”
Section: Testsmentioning
confidence: 99%